Pengaruh Promosi Kesehatan Terhadap Pengetahuan Remaja Tentang Kesehatan Reproduksi: Literature Review - Meinita Wulansari; Sri Atikah; Anggun Sasmita; Lisa Ardiningtyas (Jurnal Ventilator, 2024)
Maternal health issues refer to reproductive health issues, including comprehensive information and education on sex, contraception, access to legal and safe abortion, sexually transmitted diseases, and HIV/AIDS diagnosis. The high MMR and low understanding of reproductive health are indicators of the government's weakness in protecting and implementing the reproductive health rights of citizens. This study aims to find out how the influence of health promotion on adolescents' knowledge about reproductive health. The method used in this study is a type of literature study research. The results of the study convey that health promotion affects adolescents' knowledge about reproductive health. Adolescent reproductive health is a healthy situation that affects the organs, functions, and reproductive efforts of an adolescent. What is meant by health here is not only being free from illness or disability, but also mental, social, and cultural health. Adolescents are at high risk of various sexual and reproductive health problems, including the risk of unwanted pregnancy, the risk of sexually transmitted infections (STIs), including HIV/AIDS, unsafe abortion, and sexual violence.